Social Capital, Digital Networks and Entrepreneurship for Sustainability of Corn Farming in Lumar District, Bengkayang Regency - Usman Usman; Veneranda Rini Hapsari; Yeremia Niaga Atlantika; Sabinus Beni (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Sustainable farming systems can be implemented properly if each farm is always oriented towards an efficient production process that can be profitable and focuses on improving management and disease prevention. Social capital in social life has similarities with economic capital in society. This study aims to measure the social capital of sustainable corn farmers, namely corn farming in Tiga Berkat Village, Lumar District. The research location was determined intentionally (Purposive Method). In this study, researchers used descriptive qualitative. Qualitative research is research that is more inclined to describe by means of analysis to find meaning from events involving human life. The analysis carried out in this qualitative research is that the researcher must first understand the events that occurred by communicating directly with the source of the incident. Qualitative research can also be interpreted as research to produce and process data that describes events as they are, through interviews and observations. Results Farmers who live today expect agricultural extension workers to be more open minded about developments in information and communication technology